Adverse skin reactions following intravitreal bevacizumab injection - Ameen, S (BMJ Publishing Group, 2011)
The authors describe two separate cases of skin eruption following intravitreal bevacizumab injection with evidence to suggest that these were adverse drug reactions to bevacizumab. The authors also discuss how each case was treated and report on the final outcome.